Role of surface microstructure in forming the interaction potential between vacuum space near separated non-identical dielectric (semiconductor) nanoparticles - Ilchenko, L. G.; Lobanov, V. V.; Chuiko, A. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2006)
The structural component ΔVst(r) of the interaction potential V(r) in a vacuum inter-val dividing two dielectric (semiconductor) nanoparticles determined by the microscopic (atomic) structure of their surfaces is calculated theoretically. Within the framework of local and nonlocal electrostatics for an asymmetrical system is shown that for the narrow dividing distances L~3-20 Å the superposition of the modulated part of the potential ΔVst(r) from both surfaces promotes originating of the regions of the considerable increase (decrease) of the total potential barrier height within all the dividing interval.